Optimalisasi Perencanaan Inventori Obat di Rumah Sakit X - Manado melalui Penerapan Enterprise Resource Planning dan Minimum-Maximum Stock Level - Sondakh, Oliandes; Lonardy, Reza Richard; Mokoginta, Liany Theresia (Universitas Muhammadiyah Surakarta, 2024)
Medicine inventory management is very important in hospital operations, especially in efforts to reduce costs and ensure the availability of medications for patients. Rumah Sakit X Manado, as a Type B private hospital, adopts an Enterprise Resource Planning (ERP) system to optimize inventory planning and reduce the Days of Inventory (DOI). This research aims to analyze the application of the Minimum-Maximum Stock Level (MMSL) method in the regular drug ordering process, as well as the role of ERP in supporting drug demand projections, which impact DOI reduction. Data was collected through preliminary surveys, interviews, and analysis of drug use trends from January to September 2024. The research results showed that implementing ERP and data-based order planning reduced DOI from 19.54 days in July 2024 to 18.59 days in September 2024. Although this figure has decreased, it still has not reached the DOI target set at 16 days. Therefore, efforts are needed to increase the accuracy of demand forecasting and optimize the MMSL system to achieve better efficiency.